Institusionalisasi Ruang Belajar Alternatif dalam Masyarakat Urban: Studi Sosiologis Program Magang “Urban Islamic After-School Lab” di Surabaya - Nadlir, Nadlir; Erfansyah, Nasrul Fuad (Jurnal PUBLIQUE, 2024)
This study addresses two major issues in urban communities: the administrative and less impactful nature of university internship programs, and the absence of systematic alternative learning spaces to support elementary students facing academic difficulties at home. In urban contexts marked by limited parental time, economic pressure, and weak domestic academic assistance, community-based learning institutions are increasingly necessary. This research analyzes the institutionalization process of the “Urban Islamic After-School Lab” model as an alternative learning space integrating educational support, literacy enhancement, and Islamic values formation in Surabaya. Using action research, the study involved fourth- and fifth-grade students in Kelurahan Babad Jerawat. The research followed five stages: initial assessment, problem identification, focus group discussion, corrective action, and final assessment. The intervention emphasized reading literacy and religious literacy as foundational aspects of academic and moral development. Findings indicate that the model improved students’ literacy outcomes and transformed internships into structured social praxis, strengthening university–community engagement and revitalizing higher education’s social function in urban settings.